Customer demographics, products and customer perception towards social enterprises - Mirasol, Cicily Isabelle; Perez, Bethlynn; Safdar, Sumaiyah Rose.; Uy, Ryndenelle (2016)
The study reviews the current social enterprise landscape in Iloilo City, the activities that are currently occurring in the city, as well as the overview of the profile of social enterprises in the city, and recommends appropriate methods to increase the perception of customers towards social enterprises and their products. Two classes of respondents were part of the study: the social enterprise managers and the customers of these social enterprises. The three social enterprises that were selected as key respondent of the study were Human Nature, Leon Vegetable Growers Association, and Pera sa Basura, and a total of twenty five customer respondents were chosen as part of the analysis that is qualitative in nature, which involved descriptive statistics. The socio-demographic profile of the respondents reveal that customers purchase social enterprise products despite the age bracket. A reason for this is because the products are varied and that it answers the needs of every age class. Results also reveal that more women purchase social enterprise products because women tend to evaluate the product first before purchasing it. Also, more single individuals purchase social enterprise products because married individuals need to satisfy the basic needs of their family. Most of the social enterprises, on average, rated their products as excellent in quality, good in usefulness, good in prices and excellent in features. Customers of Human Nature rated in between excellent and good for quality and usefulness, good for price, and almost excellent for features of the products. The consumers perceive that the products that these company offer are effective and have high quality. Human Nature products are priced higher tan commercial products, however, considering that they are made from natural and organic ingredients, they still are regarded as affordable. Customers of Leon Vegetable Growers Association rate in between good and excellent for quality, almost excellent for usefulness, good for price, and almost good for features of the products. The consumers perceive that the products that these company offer are of high quality given the no-chemical ingredients of the fruits and vegetables. Most respondents believe although the products are priced high, it dues not make them indifferent to buying the products. customers of Pera sa Basura rated a little over good for quality and price, almost excellent for usefulness and good for features of the products. Most of the respondents perceived that the overall products sold by PESBA are of high quality given the intricate craftsmanship of the products. The respondents have agreed that the products are affordable and the prices are appropriate for the quality of the products. More customers today are learning towards the use of natural products because of rising awareness on social and environmental issues. The respondents, regardless of their socio-demographic profile, like the products of social enterprises because of its organic features and environmental contribution. Generally, the customers recommend to the social enterprises to engage more in promotional activities not only to increase sales but also increase awareness of the social and environmental values of the social enterprises. Additionally, improvement of the products' packaging is also recommended in order to develop the aesthetic appeal of the social enterprise products.
Research Paper (BA 199-Business Research) -- [Iloilo City : UPV-CM], May 11, 2016.